Management of Rigidity Dominant Parkinson’s Disease Through Ayurvedic Protocol (International Journal of Ayurveda and Pharma Research, 2024)
Parkinson's Disease (PD) is a disease with insidious onset and slow progression. It is a neurologic condition that causes motor manifestations namely, bradykinesia, rigidity, resting tremor, postural instability and non-motor symptoms such as depression and dementia. The modern treatment provides some symptomatic relief but any proven means for slowing the progression have not been found yet. This case is of a 64-year-old male patient who presented with complaints of slowness in daily activities, difficulty in raising left upper arm along with heaviness, tremors in both hands, difficulty in speech and movement for 3 years. Complaints were increasing progressively hindering his routine activities. He underwent our IP management for 60 days with follow-up after every 20 days. In every follow-up, the patient reported significant relief in his symptoms and after two months, he was able to perform his routine activities without any help.